CAH AMPERA: HYBRID IDENTITY OF KAMPUNG YOUTHS IN NEGOTIATING CITIZENSHIP - Subando Agus Margono (Faculty of Cultural Sciences, Universitas Gadjah Mada, 2014)
This article attempts to investigate the negotiating process for citizenship of a group of youths facing entrenched social, cultural, and political exclusion. It examines the phenomenon of citizenship negotiation based on stigmatized position of exluded youths. It was found that despite overwhelming odds, the youths use their hybrid identity, which is a manifestation of cah Ampera identity. They succeed in managing the antagonism and affiliation. The citizenship of cah Ampera ismanaged through symbolic capital and action in village micro politics. Success is reflected in their ability to manage their relations with adults, employment, and their young world.